Pengaruh Ketegangan Kerja, Kepuasan Kerja Dan Stress Kerja Terhadap Kinerja Karyawan PT Asuransi Prudential Kota Gajah - Fitriani; Sugeng; Ni Putu Indah Permata Sari (Universitas Muhammadiyah Metro, 2024)
This study aims to determine the effect of work tension, job satisfaction and job stress onemployee performance at PT Asuransi Prudential Kota Gajah. The type of research used inthis study is to use quantitative methods of survey methods. The data analysis technique usedis multiple linear regression analysis. The results showed that work tension had a positiveeffect on the performance of PT Prudential Gajah City employees. Work stress had a positiveeffect on the performance of PT Prudential Gajah City employees. Job satisfaction has apositive effect on the performance of PT Prudential Gajah City employees. Work tension, jobstress and job satisfaction simultaneously affect the performance of PT Prudential Gajah Cityemployees